PERLINDUNGAN HUKUM DATA PRIBADI APARATUR SIPIL NEGARA DALAM PENYELENGGARAAN SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK DI INDONESIA - Wafom, Alfiandri; Markus, Dwi Pratiwi (Program Studi Hukum, Universitas Muhammadiyah Sukabumi, 2026)
Digital transformation through the Electronic-Based Government System has expanded the practice of managing personal data of State Civil Apparatus by government agencies. These developments encourage efficiency, transparency, and accountability of public services, but at the same time pose a risk of leakage, misuse, and weak personal data protection guarantees. The existence of Law Number 27 of 2022 concerning Personal Data Protection has an important meaning as a normative basis for the protection of personal data of State Civil Apparatus in the implementation of electronic-based government. This study aims to analyze the legal framework for the protection of personal data of the State Civil Apparatus in the management of the Electronic-Based Government System and examine the legal responsibilities of government agencies as data controllers. The method used is normative law with a legislative text approach through literature studies of primary, secondary, and tertiary legal materials that are analyzed qualitatively by systematic, grammatical, and teleological interpretation methods. The results of the study show that Law Number 27 of 2022 provides preventive legal protection through the principles of transparency, accountability, and data minimization, as well as repressive legal protection through administrative and criminal sanctions. Government agencies bear comprehensive legal responsibilities in ensuring the security and confidentiality of personal data of State Civil Apparatus.